2006
DOI: 10.1242/jcs.03248
|View full text |Cite
|
Sign up to set email alerts
|

Influx of extracellular Ca2+ is necessary for electrotaxis inDictyostelium

Abstract: Intracellular free Ca2+ ([Ca2+](i)) is a pivotal signalling element in cell migration and is thought to be required for chemotaxis of Dictyostelium. Ca2+ signalling may also be important for electrotaxis. However this suggestion has been controversial. We show that electric fields direct Dictyostelium cells to migrate cathodally and increase [Ca2+] i in Dictyostelium cells, as determined by Fluo-3 AM imaging and Ca-45(2+) uptake. Omission of extracellular Ca2+([Ca2+](e)) and incubation with EGTA abolished the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
65
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 54 publications
4
65
1
Order By: Relevance
“…For example, based on normal chemotaxis seen in a mutant amoeba lacking an IP 3 -like receptor, it was concluded that Ca 2þ signaling was not required for chemotaxis (Traynor et al, 2000). However, diVerent groups studying the same mutant found that [Ca 2þ ] i transients dependent on Ca 2þ influx were not only retained but were required for both chemotaxis and electrotaxis (Schaloske et al, 2005;Shanley et al, 2006). In a diVerent study, it was reported that amoebae can continue their random locomotion with the same speed in the absence of [Ca 2þ ] o and the presence of 50-mM EGTA or EDTA, apparently ruling out any role for Ca 2þ influx (Korohoda et al, 2002).…”
Section: Ca 2þ Dependence Of Amoeba Locomotionmentioning
confidence: 99%
“…For example, based on normal chemotaxis seen in a mutant amoeba lacking an IP 3 -like receptor, it was concluded that Ca 2þ signaling was not required for chemotaxis (Traynor et al, 2000). However, diVerent groups studying the same mutant found that [Ca 2þ ] i transients dependent on Ca 2þ influx were not only retained but were required for both chemotaxis and electrotaxis (Schaloske et al, 2005;Shanley et al, 2006). In a diVerent study, it was reported that amoebae can continue their random locomotion with the same speed in the absence of [Ca 2þ ] o and the presence of 50-mM EGTA or EDTA, apparently ruling out any role for Ca 2þ influx (Korohoda et al, 2002).…”
Section: Ca 2þ Dependence Of Amoeba Locomotionmentioning
confidence: 99%
“…several species of fish), may be evolutionary preserved in aquatic environments as it is an excellent conductor of EF, as well as in few terrestrial organisms (e.g. monotremes, Dictyostelium, cockroaches, bees and nematode worms) [2,[5][6][7][8][9][10]. The predominant use of electrosensation and movement at desired direction is utilized for identification of food such as prey and host, to escape from potential predator and navigation to different locations in an environment.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, several cancer cells, including highly metastatic human breast cancer cells and the human prostate cancer cell line PC-3M, move to the anodal (+) pole 15,16 . Several mechanisms are proposed to mediate galvanotaxis or to explain the ability of the cells to sense the electric field, including activation of EGF receptors 12 , the epithelial sodium channel 17 , PI3K and PTEN 18 , and release of calcium ions 15,19 . The mechanism is not yet fully understood and it is possible that multiple signaling pathways are involved in galvanotaxis.…”
Section: Introductionmentioning
confidence: 99%